Pengaruh Service Quality Dan Product Quality Terhadap Customer Satisfaction Pada Rumah Makan Ayda - Agustina, Devi Citra; Rimbawan, Nyoman Dayuh (E-Jurnal Manajemen, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Under the tight competition of restaurant business, every company tries to respond and understand consumers needs, so ‘Rumah Makan Adya’ has to face the situation. In the restaurant business, service quality and product quality are indicators that indicate the range of satisfaction that customers experience, which then will result positively to the company in a long period. This research is aimed to know how much the effect of service quality and product quality have on customers satisfaction. Sampels were taken using purposive sampling method with 120 respondents. Data was analyzed using AMOS 16.0 software with Structural Equation Modelling (SEM) analysis technique. Results of analysis show that service quality and product quality have positive effect on customers satisfaction. Moreover, product quality has larger effect on customers satisfaction than service quality. Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Key words : service quality, product quality, customers satisfaction
Keywords: service quality; product quality; customer satisfaction